"Movement And Rhythm" In Physical Education Classes - Z.A.Nazarov (Genius Publishing Group, 2022)
In this article, the author suggests using a new interactive method that he has created to shape students ’attitudes towards science in physical education. In the introductory part of the lesson, students are asked to perform general development exercises using the melody, is to divide the body parts into four sections (neck, arms, waist, legs), for each section special exercises are given and they perform the exercises with applause.
Keywords: children's activities; applause; modern and non-traditional